pengaruh Pengaruh Capital Adequacy Ratio (CAR) Terhadap Financing to Deposit Ratio (FDR) - eldiani, nita (PRISMAKOM, 2024)
Financing to Deposit Ratio (FDR) growth index at one of the Sharia BPRs in Kab. Garut, namely BPR Syariah Harum Himah Nugraha, has experienced declines and increases in the last 5 years. The decline in the Financing to Deposit Ratio (FDR) is mainly thought to be due to problems in the distribution of financing which have an impact on society, especially MSMEs, causing bank installments to not run well, making it difficult for banks to control their liquidity. Several previous studies such as from Rufaidah, Djuwarsa and Danisworo (2021) show that the Capital Adequacy Ratio (CAR) has a positive and significant effect on the Financing to Deposit Ratio (FDR). This research uses quantitative research methods with a descriptive approach. Based on the research results showing simple linear regression analysis, correlation test, determination test and hypothesis test, the Capital Adequacy Ratio (CAR) has a relationship with the Financing to Deposit Ratio (FDR) with a moderate relationship direction, namely 59.6%.